Inviting Latino voters : party messages and Latino party identification - Connaughton, Stacey L., 1971- (Latino communities., 2005)
Latino's increasing numbers and their uncertain voting behaviors have enticed Democrats and Republicans to actively court this demographic group, seeking their partisan identification. Through in-depth interviews with campaign strategists, a quantitative analysis of Latino-oriented television advertisements and a survey of Latino citizens, this project examines these efforts.